ریاستِ مدینہ سے ریاست پاکستان تک: نظریہ پاکستان کا تاریخی اور فکری ارتقاء: From Medina to Pakistan: The Historical and Intellectual Evolution of the Pakistan Ideology - Muhammad Usman; Dr. Khalil Ahmad; Muhammad Ahmad (Al-Amīr Research Journal for Islamic Studies, 2025)
This research posits that the Pakistan Ideology is not merely a modern nationalist concept but represents the historical and intellectual evolution of the principles established by the first Islamic state in Medina. It argues that the Prophetic model, founded on a distinct socio-religious identity, social contract (Mi'thaq), and divine sovereignty, serves as the foundational paradigm for the genesis of Pakistan. The paper traces this ideological continuum through the centuries, analyzing the formative role of key thinkers who acted as custodians of this vision. It demonstrates how Mujaddid Alf Sani reinforced the theological boundaries; how Sir Syed Ahmad Khan translated this identity for modern political realities; how Allama Iqbal provided the philosophical dream of a state embodying Medinan ideals; and how Quaid-e-Azam actualized this dream through constitutional struggle. Employing a historico-analytical methodology, the study concludes that the creation of Pakistan was the logical culmination of a 1400-year intellectual inheritance, re-affirming the original Medinan model of statehood in the 20th century. Keywords: Pakistan Ideology, State of Medina, Intellectual Evolution, Two-Nation Theory, Muslim Sovereignty